A modified isotope-based method for potential high-frequency evapotranspiration partitioning. (February 2022) - Yuan, Yusen; Wang, Lixin; Wang, Honglang; Lin, Wenqing; Jiao, Wenzhe; Du, Taisheng
Highlights: A modified isotope-based method was developed to estimate the evapotranspiration partitioning, and it can be applied on various time scales. The modified method and the traditional method are equivalent at a 15-minute time scale. The modified method is capable of partitioning evapotranspiration at high-frequency and distributed the high sensitivity parameter δET into other three less sensitive parameters. The high-frequency method is advantageous in avoiding the extrapolation of the keeling plot regression line, and enabling the calculation of confidence interval of evapotranspiration partition. The high-frequency method might be useful when investigating evapotranspiration partitioning under short-term extreme weather events and flush agricultural irrigation. Abstract: To better understand water and energy cycles, numerous efforts to partition evapotranspiration (ET) into evaporation (E) and transpiration (T) have been made over the recent half century. One of the analytical methods is the isotopic approach. The isotopic composition of ET (δET ) is a crucial parameter in the traditional isotope-based ET partitioning model, which however, has considerable uncertainty and high sensitivity. Here we proposed a modified T fraction in total ET (FT ) calculation using Keeling plot slope (k), the atmospheric vapor concentration (Cv ), and the isotopic composition of atmospheric vapor (δv ), to avoid the direct use of δET . Following the traditional method, we used the Craig-Gordon model for the isotopic composition of evaporation (δE ) and chamber method for the isotopic composition of transpiration (δT ) in our modified method. The modified FT calculation method (FT (m)) can be applied at a 15-min time scale using the average values (FTi (mp)) and at a 1 Hz time scale for high-frequency method (FTi ). The modified method was verified by both theoretical derivations and field observations. FTi (mp) was equivalent to those using the traditional isotopic method at a 15-min time scale. However, FTi eliminated the highly sensitive parameter δET, and redistributed the sensitivity of δET into three less sensitive parameters. Additionally, FTi has two main advantages. First, the high-frequency method avoids the extrapolation of the Keeling plot regression line intercept. Second, the high-frequency method can produce a 95% confidence interval of FT in a measurement cycle (e.g., 15 min). The calculated confidence interval was different from that of traditional uncertainty analysis. The high-frequency method might be useful when investigating evapotranspiration partitioning under short-term extreme weather events and flush agricultural irrigation.